The Importance of “Outsiders” in Small Firm Strategic Planning - Robinson, Richard B. (Academy of Management Journal, 1982)
The value of ?outsider-based? strategic planning for small firms is empirically examined using a sample of firms engaging in outsider-based planning and two control groups. The effectiveness of small firms engaging in outsider-based strategic planning was significantly higher than that of firms that did not engage in such planning.